ANALYSIS OF PRODUCTION AND DISTRIBUTION THE BUSINESS OF DRIED FISH PROCESSING GULAMAH (PSEUDOCIENNA AMOVENSIS) IN THE KELURAHAN BELAWAN BAHARI MEDAN BELAWAN SUBDISTRIC MEDAN CITY NORTH SUMATRA - Riniyanti Panjaitan; Hendrik '; Darwis ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in July 2016, it was conducted in the Kelurahan of Belawan Bahari Medan city. This study aimed to analyze the production of Salted Fish Gulamah in Kelurahan Belawan Bahari starting from production inputs, production process, product of dried fish Gulamah, and analyze the distribution of salted fish Gulamah in District Belawan Bahari. The method used in this research is survey method and determine the respondents using the method applied bassed on population (Arikunto 2006).Based on the research results, for the production of salted fish Gulamah input using Gulamah fresh fish, the process includes several stages and the product is a salted fish Gulamah. Gulamah salted fish production in Kelurahan Belawan Bahari by 27 business units with an average production of salted fish once a production of 3 tons, with an average per month is 68.6 tons. Distribution of salted fishGulamah markets include in area Medan and some areas the city of Medan, Dairi, Deli Serdang, Labuhan Batu, Tapanuli Selatan, Tapanuli Tengah, Serdang Bedagai and Rantau Parapat with the distribution percentage of 40% over the market in the city of Medan and 60% outside the Medan market.Keywords: Production, Distribution, Gulamah Salted Fish, Kelurahan Belawan Bahari